Synthesis and bio-evaluation of xylan-5-fluorouracil-1-acetic acid conjugates as prodrugs for colon cancer treatment. (10th February 2017) - Sauraj,; Kumar, S. Uday; Gopinath, P.; Negi, Yuvraj Singh
Highlights: Xyl-5-FUAC conjugates were synthesized as prodrugs for colon specific drug delivery. Higher amount of drug was released from the conjugates in presence of colonic contents. Xyl-5-FUAC conjugates shows better cytotoxicity than free drug. Abstract: In the present study, xylan-5-fluorouracil-1-acetic acid (Xyl-5-FUAC) conjugates as colon specific prodrugs were synthesized and evaluated by in-vitro release study. The chemical stability of the conjugates was performed in acidic (pH 1.2) and basic buffers (pH 7.4), which showed their stability in upper gastrointestinal tract. The in-vitro drug release profiles of the conjugates were studied in the presence of rat's gastrointestinal contents. The results showed that the low amounts of drug 3–4% and 5–7% were released in gastric and small intestine contents respectively, while 53–61% of the drug was released in cecum and colonic contents. The cytotoxicity studies of the conjugates were also evaluated on human colorectal cancer cell line (HTC-15 and HT-29), which showed that the conjugates are more cytotoxic than the free drug. Therefore the results reveal that Xyl-5-FUAC conjugates are potential candidates for colon specific drug delivery in the treatment of colonic cancer with minimal undesirable side effects.